Manajemen Peserta Didik Sekolah Dasar: Konsep, Implementasi, dan Strategi Optimalisasi - Nalle, Anselmus; Unggin, Elisabet Angela; Wadu, Juanita Aristia; Molum, Januario Jacsem; Rizmawan, Yosef Cendy; Dua Lehan, Andriyani A.; Dethan, Jimylton (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2024)
Student management is an important aspect in creating an effective learning environment in elementary schools. This article aims to discuss the concept, implementation and optimization strategy for student management in elementary schools. Using a qualitative descriptive approach, this article reviews the planning, organizing, implementing and evaluating student management, as well as the challenges faced. The conclusion of this article emphasizes the importance of collaboration between schools, parents and the community in realizing holistic educational goals.